Regulation of the FOXM1 transcription factor by the estrogen receptor α at the protein level, in breast cancer - Karadedou, C T (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2006)
Breast cancer is the most frequent type of cancer of women in the western world. Antiestrogens, including Tamoxifen (OHT) and Faslodex (ICI), are widely used in the endocrine treatment of breast cancer. However, the majority of breast cancers are either resistant to endocrine therapy or eventually become unresponsive to antiestrogen therapy. Better understanding of the molecular mechnisms that govern tumour proliferation, is therefore needed to develop new therapies for the disease. The Forkhead family of transcription factors plays an important role in regulating cell proliferation, cell death and differentiation.The estrogen receptor (ER) a positive breast carcinoma cell line MCF-7 and the ERa negative line MDA-MB-231 was used to study the potential regulation of the Forkhead member FOXM1 by ER. It was indicated that estrogen and ER regulate the expression of FOXM1 at the protein level. Since Forkhead proteins play an important role in regulating cell proliferation, cell death and differentiation, this study helps to explain some of the functions of ER in tumourigensis, and the way these Forkhead proteins could be crucial targets for therapeutic strategies and/or markers for diagnosis and prognosis.